Erlotinib induced ectropion following papulopustular rash - SALMAN, ANDAÇ; SEÇKİN GENÇOSMANOĞLU, DİLEK; ÇERMAN, EREN (SPECJALISCI DERMATOLODZY, 2015)
Background: Erlotinib is a targeted anti-cancer drug which acts through the inhibition of epidermal growth factor receptor (EGFR). Main observations: A 79-year-old developed bilateral ectropion after he received erlotinib treatment for lung adenocarcinoma. The ectropion completely resolved with symptomatic treatment without any modification in erlotinib therapy. Conclusions: EGFR inhibitors are frequently associated with a variety of mucocutaneous adverse events. Ocular toxicity associated with these agents has been reported rarely. We present this case to underline the importance of recognition of newly reported cutaneous and ocular adverse events of targeted therapies.
Keywords: adverse effects; ectropion; eye; erlotinib; papulopustular rash; FACTOR RECEPTOR INHIBITORS; CICATRICIAL ECTROPION; TOXICITIES